Pemberian Makanan Tambahan Fitbar Bingu (Ubi ungu) Terhadap Status Gizi Balita Wasting Di Puskesmas Sako Tahun 2021 - Dyah Aulia Hapsari; Terati Terati; Yunita Nazarena; Susyani Susyani; Nathasa Weisdania Sihite (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2021)
Background : Wasting is a lack of weight for height so that the child body is not proportional (low weight for height). Data obtained from UNICEF/WHO/World Bank Group ini 2017 shows that in 2016 the prevalence of wasting was 7,7%. The high prevalence is still needed, one of which is the provision of additional food. Purple potatoes (lpomoea batatas var A) is a type of tubers high in energy sources for the body while tempeh is a source of protein that is easily digested by the body. So both of these foods can be used as a modification to provide additional food for children under five. This pre test and post test research with control group Purpose : aims to determine the effect of PMT fitbar bingu (purple sweet potato) on weight changes of under five wasting at under five wasting at Sako Health Center, Palembang City. Methods :The research is toddlers who are weighed at Sako Health Center and wasting totaling 93 people. Data collection was carried out using digital scales, microtoice, and a 24 hour recall form. The data analysis used was univariate and bivariate analysis.The results showed that some of the respondents were male 61,6% with age 18-57 months. From the result of statistical tests, the avarage body weight in the treatment group was 10,18 kg to 11,12 kg, while the comparison avarage body weight was 10,51 kg to 10,61 kg. The difference in body weight change in the treatment group was 0,24 kg while the comparison group was 0,10 kg, with the results of statistical tests (t independent p value = 0,000) Conclusioin : changes in weight of wasting children at Sako Palembang Health Center. Suggestion: Further research needs to be done to see changes in the nutritional status of children by giving additional food with a fitbar for a longer time so that it will look more significant.